Symptoms of Survivors of Pediatric Hematopoietic Stem Cell Transplant by Age, Sex, and Transplant Type. (September 2022) - Morrison, Caroline F.; Drake, Sarah; Basile, Nathan L.; Horn, Mary Jane; Lambert, Joshua; Myers, Kasiani C.; Pai, Ahna L.H.
Purpose: The purpose of this study was to describe symptoms experienced by survivors of pediatric hematopoietic stem cell transplant (HSCT), and demographic and treatment-factors associated with ongoing symptomology.Methods: Fifty pediatric survivors completed a cross-sectional pilot study. Questionnaires were administered online via REDCap to assess symptoms experienced in the last week. Survivors also consented to a medical record chart review.Results: Survivors were on average 5.4 years post-HSCT (range 1.1 to 9 years), male (58%), and Caucasian (80%) who received an allogeneic HSCT (92%). The most commonly reported symptoms were difficulty concentrating (42.5%), pain (38%), worry (38%), nervousness (37.5%), and lack of energy/fatigue (34%). Survivors reported up to 14 symptoms, with 90% of the sample experiencing at least one symptom in the previous week. Average number of symptoms varied by age group between 2.1 (8–9 years) and 6.8 (18 and older). Age and female gender were associated with higher levels of fatigue.Conclusions: The majority of survivors experienced at least one symptom in the previous week. Neuropsychological symptoms and pain endure well into survivorship that can influence outcomes such as function and health-related quality of life (HRQOL). Research is needed on biological mechanisms of ongoing symptomology, effective interventions to prevent or mitigate symptoms, and the impact of symptoms on patient outcomes including daily functioning and HRQOL.Implications Survivors of pediatric HSCT continued to experience symptoms for up to nine years. Survivors should be frequently screened for symptoms, as symptoms may affect function, learning/employment outcomes, and HRQOL.